Intrinsic microporous material, protection of lithium metal negative electrode, lithium metal negative electrode, solid electrolyte and battery

By using intrinsic microporous materials prepared from 4,4'-dihydroxybiphenyl and 2,2,2 trifluoroacetophenone in lithium metal batteries as artificial SEI films or solid electrolyte mixed with polyethylene oxide, the The problems of SEI film rupture and lithium dendrites during the circulation of lithium metal batteries improve the circulation performance and safety of the battery.

CN119264346APending Publication Date: 2025-01-07HEBEI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411384234.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The problems of rupture and recombination of native SEI films and growth of lithium dendrites during the circulation process lead to shortening of cycle life and safety hazards. The existing solid electrolyte materials have low ionic conductivity and poor mechanical properties, which limit their application.

Method used

Intrinsic microporous materials prepared by superacid catalytic reactions of 4,4'-dihydroxybiphenyl and 2,2,2 trifluoroacetophenone are coated on the surface of lithium metal negative electrodes as artificial SEI films, or with polyethylene oxide Solid electrolytes are prepared by mixing them to form rich microporous structures to improve the mechanical strength and ionic conductivity of the electrolyte.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, improve the circulation performance and safety of lithium batteries, extend battery life, reduce the occurrence of side reactions, and enhance the chemical stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264346A_ABST
    Figure CN119264346A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium batteries, and discloses an inherent microporous material, protection of a lithium metal negative electrode, the lithium metal negative electrode, a solid electrolyte and a battery. The inherent microporous material is prepared from a monomer 1 and a monomer 2 through a super-acid catalytic reaction; the monomer 1 is 4, 4 '-dihydroxybiphenyl and / or bisphenol AF; and the monomer 2 is 2, 2, 2-trifluoroacetophenone. According to the invention, the inherent microporous material can be used as an artificial SEI film to be coated on the surface of the lithium metal negative electrode, and the inherent microporous material can be mixed with polyoxyethylene to prepare the solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and more specifically, relates to an inherent microporous material and protection of a lithium metal negative electrode and a lithium metal negative electrode and a solid electrolyte and a battery. Background Art

[0002] With the rapid development of electronic products and electric vehicles, people's requirements for lithium battery performance have gradually increased, and current lithium-ion batteries have reached their theoretical limits. Although traditional lithium-ion batteries have achieved excellent cycle performance through chemical embedding technology, the low theoretical capacity of graphite cathodes limits the energy density of batteries. In contrast, the theoretical capacity of lithium metal (3860mAh / g) is ten times that of graphite (372mAh / g). Therefore, lithium metal is regarded as the best choice for the next generation of high energy density lithium batteries.

[0003] Lithium metal anodes have been widely studied in both liquid electrolyte batteries and all-solid-state batteries. The advantage of liquid electrolyte lithium metal batteries is that the electrode-electrolyte interface has fast ion transport and mature production processes. However, there are still many challenges in the practical application of this type of battery. For example, lithium metal, as an active metal, can react violently with oxygen and water. The most important thing in the lithium metal battery system is to avoid contact with water and oxygen. The lithium metal anode is initially silver-white, but after a period of operation, the surface of the lithium sheet turns black and there are some cracks and detached "dead lithium". This is because the native SEI film on the surface of the lithium metal anode expands rapidly in volume during the cycle, the native SEI film ruptures, and a large number of lithium dendrites grow in the gaps. The cycle repeats, and the native SEI film continues to rupture and reorganize, which will eventually shorten the battery cycle life and even cause safety problems.

[0004] The current lithium anode protection strategies are:

[0005] 1) Three-dimensional current collector modification to create nano-microporous structure;

[0006] 2) Electrolyte optimization: by adding inhibitors and optimizing electrolyte composition, the cycle life can be extended;

[0007] 3) Diaphragm modification, by functionalizing the surface of the negative end of the diaphragm to change the growth direction of lithium dendrites and thus inhibit the further growth of lithium dendrites;

[0008] 4) Artificial SEI film, which inhibits the growth of lithium dendrites by modifying the surface of lithium negative electrode;

[0009] 5) Solid electrolytes: Replacing organic electrolytes with non-flammable solid electrolytes can solve the potential safety problems of batteries at the source. Polyethylene oxide (PEO) is a promising solid-state lithium battery electrolyte material, but its low inherent ionic conductivity, poor mechanical properties, and inability to prevent the shuttling effect of polylithium ions limit its application.

[0010] Therefore, it is urgent to propose a new intrinsic microporous material to improve the poor cycle performance, low coulombic efficiency and safety issues of lithium metal batteries. Summary of the invention

[0011] The purpose of the present invention is to address the deficiencies of the prior art and to provide an inherent microporous material and protection of a lithium metal negative electrode and a lithium metal negative electrode and a solid electrolyte and a battery. The present invention can use the inherent microporous material as an artificial SEI film coated on the surface of the lithium metal negative electrode, and can also use the inherent microporous material mixed with polyethylene oxide to prepare a solid electrolyte.

[0012] In order to achieve the above-mentioned object, the first aspect of the present invention provides an intrinsic microporous material, wherein the intrinsic microporous material is prepared by a superacid catalytic reaction of monomer 1 and monomer 2;

[0013] The monomer 1 is 4,4′-dihydroxybiphenyl and / or bisphenol AF;

[0014] The monomer 2 is 2,2,2-trifluoroacetophenone.

[0015] According to the present invention, preferably, the micropore diameter of the intrinsic microporous material is 0.4-2.0 nm.

[0016] According to the present invention, preferably, the molar ratio of the monomer 1 to the monomer 2 is 1:(0.5-2).

[0017] According to the present invention, preferably, the superacid catalytic reaction comprises: mixing monomer 1 and monomer 2 with dichloromethane and trifluoromethanesulfonic acid aqueous solution and sequentially stirring, washing and drying to obtain the inherent microporous material.

[0018] In the present invention, the purity of the trifluoromethanesulfonic acid aqueous solution is 98%-99.99%.

[0019] According to the present invention, preferably, the solvent used for the washing is an alcohol solvent and / or an ether solvent.

[0020] A second aspect of the present invention provides a method for protecting a lithium metal negative electrode, the method comprising:

[0021] S1: mixing and dispersing the inherent microporous material and the first protective solvent to obtain a protective mixed solution;

[0022] The inherent microporous material is the inherent microporous material described;

[0023] S2: coating the protective mixed solution on the surface of the lithium metal negative electrode and performing a drying process to obtain a lithium metal negative electrode covered with an artificial SEI film.

[0024] In the present invention, monomer 1 and monomer 2 are used to prepare intrinsic microporous materials (PIMs materials) with rich, interconnected, and permanent microporous structures through superacid catalytic reactions. As an organic material with rigid chains, PIMs have both rigidity and flexibility, which meets the requirements of an ideal artificial SEI membrane. The micropore diameter of PIMs is 0.4-0.8nm, which is evenly distributed in the polymer matrix, and constructs an isotropic channel network for the diffusion of lithium ions. In addition, the PIMs material prepared by the present invention contains a large number of -CF3 functional groups. Due to the strong electronegativity of CF3, it exhibits a strong interaction with lithium ions, promotes the absorption of electrolytes, and reduces the occurrence of side reactions. At the same time, its nanoscale pore size regulates the migration path of lithium ions, which is beneficial to the uniform deposition of lithium ions and inhibits the growth of dendrites.

[0025] According to the present invention, preferably, the first protective solvent is anhydrous acetonitrile and / or N-methylpyrrolidone.

[0026] According to the present invention, preferably, the concentration of the intrinsic microporous material in the protective mixed solution is 1-2 wt %.

[0027] According to the present invention, preferably, the coating amount of the protective mixed solution on the surface of the lithium metal negative electrode is 15-40 μL·cm -2 .

[0028] According to the present invention, preferably, the protective dispersion is coated on the surface of the lithium metal negative electrode by scraping, spraying, spin coating or drop coating.

[0029] In the present invention, the inherent microporous material can be dissolved in the first protective solvent. The excellent moldability of the inherent microporous material can be directly dripped on the lithium metal sheet, well covering the lithium metal sheet, and forming an in-situ protective film on the surface of the lithium metal sheet to avoid "agglomeration" and "uneven distribution". This in-situ protective film can not only enhance the chemical stability of the material, but also play a role continuously during the operation of the battery.

[0030] The third aspect of the present invention provides a lithium metal negative electrode covered with an artificial SEI film obtained by the protection method of the lithium metal negative electrode.

[0031] A fourth aspect of the present invention provides a lithium metal-based battery, wherein the negative electrode of the battery is the lithium metal negative electrode covered with the artificial SEI film.

[0032] According to the present invention, preferably, the electrolyte of the battery is at least one of a carbonate electrolyte including a lithium salt, an ether electrolyte including a lithium salt, a sulfone electrolyte including a lithium salt, and a carboxylate electrolyte including a lithium salt.

[0033] According to the present invention, preferably, the lithium salt is at least one of lithium nitrate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate and lithium hexafluoroarsenate.

[0034] According to the present invention, preferably, the lithium metal-based battery is a lithium-lithium symmetrical battery, a lithium-copper half-cell, a lithium ion battery, a lithium solid-state battery, a lithium sulfur battery, a lithium oxygen battery, a lithium nitrogen battery or a lithium carbon dioxide battery.

[0035] A fifth aspect of the present invention provides a method for protecting a lithium metal negative electrode, the method comprising:

[0036] (1) mixing an intrinsic microporous material, lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide, and a second protective solvent to prepare a mixed slurry;

[0037] The inherent microporous material is the inherent microporous material described;

[0038] (2) The mixed slurry is coated on the surface of a polytetrafluoroethylene plate and dried to obtain a solid electrolyte.

[0039] In the present invention, the molecular weight of the polyethylene oxide is 1×10 5 -1×10 7 The purity of the lithium bis(trifluoromethanesulfonyl)imide is 98%-99.99%.

[0040] In the present invention, the present invention utilizes monomer 1 and monomer 2 to prepare PIMs with rich, interconnected, and permanent microporous structures through superacid catalysis reaction. PIMs are used as organic frameworks to form composite electrolytes to comprehensively improve the performance of polyethylene oxide (PEO). The unique structure of PIMs not only improves the mechanical strength and hardness of the PEO electrolyte by an order of magnitude, increases the stability to the metal lithium cathode, but also improves its ionic conductivity by reducing the crystallinity. The PIMs of the present invention have high mechanical strength and certain flexibility, can effectively cope with the volume change of the electrode during the charge and discharge process, avoid the rupture and failure of the SEI layer, and are crucial to maintaining the long-term stable operation of the battery.

[0041] According to the present invention, preferably, the second protective solvent is an anhydrous pure solvent, preferably at least one of anhydrous acetonitrile, N-methylpyrrolidone, chloroform, dimethyl sulfoxide and N,N-dimethylformamide.

[0042] According to the present invention, preferably, the mass fraction of the inherent microporous material in the mixed slurry is 5-20%; the molar ratio of lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide in the mixed slurry is 1:(10-30); and the mass ratio of the inherent microporous material to polyethylene oxide is 1:(5-20).

[0043] According to the present invention, preferably, the film thickness of the mixed slurry on the surface of the polytetrafluoroethylene plate is 40-100 nm. In the present invention, the mixed slurry is evenly spread on the surface of the polytetrafluoroethylene plate with a scraper, and the thickness of the scraper when applying is 50-500 μm. As a preferred embodiment, the present invention cuts the obtained solid electrolyte into discs with a diameter of 10-20 mm.

[0044] A sixth aspect of the present invention provides a solid electrolyte obtained by the lithium metal negative electrode protection method.

[0045] A seventh aspect of the present invention provides a lithium metal-based battery, wherein the electrolyte of the battery is the solid electrolyte described above.

[0046] According to the present invention, preferably, the lithium metal-based battery is a lithium-lithium symmetrical battery, a lithium-copper half-cell, a lithium ion battery, a lithium solid-state battery, a lithium sulfur battery, a lithium oxygen battery, a lithium nitrogen battery or a lithium carbon dioxide battery.

[0047] The beneficial effects of the technical solution of the present invention are as follows:

[0048] The present invention can use the inherent microporous material as an artificial SEI film coated on the surface of the lithium metal negative electrode, and can also use the inherent microporous material to mix with polyethylene oxide to prepare a solid electrolyte, so as to solve the problems of rupture and recombination of the original SEI film and inhibition of the growth of lithium dendrites occurring during the cycle of the lithium metal battery, improve the performance of the lithium battery, and solve the battery safety hazards from the source.

[0049] The intrinsic microporous material (PIMs material) provided by the present invention is rarely reported in the field of artificial SEI membrane and solid electrolyte, opens up a new way for the design and optimization of lithium batteries, and has broad application prospects.

[0050] The preparation method of the intrinsic microporous material (PIMs material) of the present invention is simple, the operation is simple, the raw materials are easily available, and the production cost is low and the output is high, so the material is suitable for commercial production.

[0051] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.

[0053] Figure 1 The XRD patterns of the PIMs materials prepared in Examples 1 and 2 of the present invention are shown (“Intensity” is intensity, “2θ (degree) is angle”).

[0054] Figure 2 The Fourier infrared spectra (“Transmittance” transmittance, “Wavenumbers” wavenumber) of the PIMs materials prepared in Examples 1 and 2 of the present invention are shown.

[0055] FIG. 3 shows the hydrogen spectra of the PIMs materials prepared in Examples 1 and 2 of the present invention ( Figure 3A is the hydrogen spectrum of Example 1, Figure 3B It is the hydrogen spectrum of Example 2; "a, b, c, d, e, f" represent the peaks represented by the bonds in the material structure, which are used to prove that an inherent microporous polymer has been synthesized; n represents the degree of polymerization; CDCl3 is the solvent for the test).

[0056] FIG. 4 shows the SEM images of the PIMs materials prepared in Examples 1 and 2 of the present invention ( Figure 4A is the SEM picture of Example 1, Figure 4B is the SEM image of Example 2).

[0057] FIG. 5 shows the results of constant current charge and discharge tests of assembled battery devices according to Examples 3 and 4 of the present invention ( Figure 5A The test results of the battery device of Example 3; Figure 5B The test results of the battery device of Example 4; "LiBare" is a lithium-lithium symmetric battery (control group) assembled from a blank lithium metal negative electrode without artificial SEI film protection; "Voltage" is voltage, and "Time" is time).

[0058] Figure 6 The figure shows the coulombic efficiency test results of the assembled battery device in Example 5 of the present invention ("BareCu" is a lithium-copper half-cell (control group) assembled from a blank lithium metal negative electrode without artificial SEI film protection; "Coulombic Efficiency" is the coulombic efficiency; "Cycle Number" is the number of cycles).

[0059] Figure 7The constant current charge and discharge test results of the assembled battery device in Example 6 of the present invention are shown (wherein, "Bare Li" is a lithium-lithium symmetric battery (control group) assembled from a blank polyethylene oxide solid electrolyte; "Voltage" is voltage, and "Time" is time). DETAILED DESCRIPTION

[0060] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0061] In the following embodiments:

[0062] 4,4′-dihydroxybiphenyl was purchased from Anergy, 100, 98%;

[0063] 2,2,2-Trifluoroacetophenone was purchased from MacLean, 100 g, 99%;

[0064] Trifluoromethanesulfonic acid was purchased from Maclean, 100 g (AR, 98.0%);

[0065] Polyethylene oxide was purchased from Maclean, 25 g, 2×10 6 ;

[0066] Lithium bis(trifluoromethanesulfonyl imide) was purchased from MacLean, 100 g, 99%.

[0067] Example 1

[0068] This embodiment provides an intrinsic microporous material, wherein the intrinsic microporous material is prepared by a superacid catalytic reaction of monomer 1 and monomer 2;

[0069] The monomer 1 is 4,4′-dihydroxybiphenyl;

[0070] The monomer 2 is 2,2,2-trifluoroacetophenone.

[0071] The superacid catalytic reaction includes: adding 4,4′-dihydroxybiphenyl (0.9 g, 4.8 mmol), 2,2,2-trifluoroacetophenone (0.8 g, 4.8 mmol), dichloromethane (7 mL) and trifluoromethanesulfonic acid (1 mL) into a 20 mL round-bottom flask, stirring at room temperature for about 3-4 hours until the solution becomes viscous. The viscous solution is poured into a methanol / water mixture, the precipitated polymer is collected by filtration, and thoroughly washed with methanol and water to obtain the inherent microporous material, i.e., white fiber PX-BP, wherein the micropore diameter of the inherent microporous material is 0.4-2.0 nm.

[0072] The specific reaction equation is as follows:

[0073]

[0074] Example 2

[0075] This embodiment provides an intrinsic microporous material, wherein the intrinsic microporous material is prepared by a superacid catalytic reaction of monomer 1 and monomer 2;

[0076] The monomer 1 is bisphenol AF;

[0077] The monomer 2 is 2,2,2-trifluoroacetophenone.

[0078] The superacid catalytic reaction comprises: adding bisphenol AF (1.7 g, 4.8 mmol), 2,2,2-trifluoroacetophenone (1.1 g, 6.28 mmol), dichloromethane (5 mL) and trifluoromethanesulfonic acid (4 mL) into a 20 mL round-bottom flask, stirring at room temperature for about 3-4 hours until the solution becomes viscous. The viscous solution is poured into a methanol / water mixture, the precipitated polymer is collected by filtration, and thoroughly washed with methanol and water to obtain the inherent microporous material, i.e., white fiber PX-HFP (whiter than PX-BP in Example 1), and the micropore diameter of the inherent microporous material is 0.4-2.0 nm.

[0079] The specific reaction equation is as follows:

[0080]

[0081] like Figure 1 As shown in FIG. 1 , the XRD patterns of the PIMs materials prepared in Examples 1 and 2 are used to study the polymer chain filling behavior of the artificial SEI film of the present invention by using wide angle X-ray diffraction (WAXD). Figure 1 As shown in Figure 2, each artificial SEI film exhibits two broad halos instead of sharp peaks, indicating the amorphous chain packing of the material. Specifically, the first broad halo in the range of 10.8–12.6° of 2θ represents the The d-spacing value (peak width) of PX-HFP in Example 2 is much larger than that of PX-BP in Example 1, which is This is due to the fact that the large amount of CF3 groups inhibits segment stacking and increases the segment distance.

[0082] like Figure 2 As shown, it is the Fourier infrared spectrum of the PIMs material prepared in Examples 1 and 2. Figure 2In the infrared spectrum, the peak intensity is an indicator of the amount of infrared absorption. When the absorption intensity of a peak is higher and wider, it means that the relative content of molecules in the characteristic vibration mode is greater and the molecular distance is smaller. The peak of PX-HFP is shorter than that of PX-BP because PX-HFP contains more fluorine, which increases the repulsion between molecules and increases the molecular distance.

[0083] As shown in FIG. 3 , it is the hydrogen spectrum of the PIMs material prepared in Examples 1 and 2. The peak corresponding to the PIMs material can be found in the hydrogen spectrum, proving that the PIMs material is successfully prepared.

[0084] As shown in FIG. 4 , it is a SEM image of the PIMs material prepared in Examples 1 and 2. It can be clearly seen from FIG. 4 that the surface of the artificial SEI film is smooth and dense, with almost no visible defects.

[0085] Example 3

[0086] This embodiment provides a method for protecting a lithium metal negative electrode, the method comprising:

[0087] S1: The intrinsic microporous material PX-BP of Example 1 is mixed and dispersed with anhydrous N-methylpyrrolidone to prepare a protective mixed solution; the concentration of the intrinsic microporous material in the protective mixed solution is 1wt%;

[0088] S2: Use a pipette to transfer 40 μL of the protective mixed solution, and apply it twice on the surface of a lithium metal negative electrode disc with a diameter of φ10 mm, and dry it under vacuum at room temperature to obtain a lithium metal negative electrode covered with an artificial SEI film.

[0089] This embodiment also provides a lithium metal-based battery, specifically:

[0090] A lithium-lithium symmetric battery is assembled using the lithium metal negative electrode covered with the artificial SEI film of this embodiment;

[0091] Adopt polypropylene diaphragm;

[0092] The electrolyte is LiTFSI / DME-DOL (i.e., dimethyl ether (DME) and 1,3-dioxolane (DOL) are mixed in a volume ratio of 1:1 to form a mixed solution; lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is added to the mixed solution, and the concentration of LiTFSI in the electrolyte solution is 1.0 M; anhydrous lithium nitrate is added to the above electrolyte solution, and the concentration of anhydrous lithium nitrate in the electrolyte solution is 2 wt%);

[0093] Assemble into a CR2032 button battery.

[0094] Example 4

[0095] This embodiment provides a method for protecting a lithium metal negative electrode. The only difference between this embodiment and embodiment 3 is that the inherent microporous material is the PX-HFP of embodiment 2, and a lithium metal negative electrode covered with an artificial SEI film is obtained.

[0096] This embodiment also provides a lithium metal-based battery. The only difference between this embodiment and Embodiment 3 is that the lithium metal negative electrode covered with the artificial SEI film of this embodiment is used for assembly.

[0097] Example 5

[0098] This embodiment provides a lithium metal-based battery. The only difference between this embodiment and embodiment 4 is that this embodiment assembles a lithium-copper half-cell.

[0099] Example 6

[0100] This embodiment provides a method for protecting a lithium metal negative electrode, the method comprising:

[0101] S1: mixing the intrinsic microporous material PX-BP of Example 1 with lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and anhydrous acetonitrile to prepare a mixed slurry;

[0102] The mass fraction of the inherent microporous material in the mixed slurry is 10%; the molar ratio of lithium bis(trifluoromethanesulfonyl)imide to polyethylene oxide in the mixed slurry is 1:20; the mass ratio of the inherent microporous material to polyethylene oxide is 1:10;

[0103] S2: Use a scraper to evenly spread the mixed slurry on the surface of the polytetrafluoroethylene plate to a thickness of 50-500 μm, then dry it and cut it into discs with a diameter of 18 mm to obtain a solid electrolyte. The film thickness of the mixed slurry on the surface of the polytetrafluoroethylene plate is 60 nm.

[0104] This embodiment also provides a lithium metal-based battery, which is a lithium-lithium solid-state battery, and the electrolyte of the battery is the solid-state electrolyte described in this embodiment.

[0105] Test Example 1

[0106] In this test example, the battery devices assembled in Examples 3 and 4 were placed in a constant temperature box at 25°C for 8 hours, and then a constant current charge and discharge test was performed on a blue electric test system (the test conditions include: the current density is 10 mA·cm -2 , discharge depth is 5mAh·cm -2 );

[0107] In this test example, a blank lithium metal negative electrode without artificial SEI film protection was also set as a control group.

[0108] The test results are shown in Figure 5, from which it can be seen that:

[0109] The polarization voltage of the lithium-lithium battery protected by the PIMs materials prepared in Examples 1 and 2 reached a stable state after 300 hours of cycling, and there was no trend of polarization potential growth in the subsequent cycles, and the performance was stable; the lithium-lithium battery in the control group showed a serious increase in polarization potential after 250 hours of cycling, and was completely ineffective after about 500 hours. This shows that coating the PIMs materials prepared in Examples 1 and 2 on the surface of the lithium metal negative electrode to construct an artificial SEI film can effectively reduce the excessive polarization potential of the battery during the charging and discharging process, effectively inhibit the growth of lithium dendrites, thereby achieving effective protection of the lithium metal negative electrode and significantly improving the cyclic performance of the lithium metal battery.

[0110] Test Example 2

[0111] In this test example, the battery device assembled in Example 5 was tested for coulombic efficiency (test conditions include: current density of 1 mA·cm -2 , the deposition amount is 1 mAh cm -2 );

[0112] In this test example, a blank lithium metal negative electrode without artificial SEI film protection was also set as a control group.

[0113] Test results such as Figure 6 As shown, it can be seen that:

[0114] The lithium metal battery modified with the PIMs material prepared in Example 2 has a lower nucleation overpotential and maintains a coulombic efficiency of more than 90% after 100 cycles, while the lithium metal battery in the control group has a worse cycle stability. The coulombic efficiency of the lithium-copper battery in the control group without intrinsic microporous material protection dropped to 90% after 73 cycles, which is much lower than the coulombic efficiency of the lithium metal battery with the negative electrode protected by the intrinsic microporous material prepared in Example 2.

[0115] Test Example 3

[0116] In this test example, the battery device assembled in Example 6 was placed in an oven at 60°C for 8 hours, and then a constant current charge and discharge test was performed on a blue electric test system (the test conditions included: the current density was 0.1 mA·cm -2 , the discharge depth is 0.1mAh·cm -2 );

[0117] In this test example, a blank polyethylene oxide solid electrolyte was also set as a control group.

[0118] Test results such as Figure 7 As shown, it can be seen that:

[0119] The polarization voltage of the lithium-lithium battery protected by the PIMs material prepared in Example 1 shows a decreasing trend during cycling, and can be stably cycled for more than 300 hours with stable performance; the lithium-lithium battery in the control group has a serious short circuit phenomenon after cycling for about 200 hours, until it completely fails. This shows that the solid electrolyte prepared by the PIMs material prepared in Example 1 can effectively reduce the polarization voltage of the battery during the charging and discharging process, and inhibit the growth of lithium dendrites, thereby achieving effective protection of the lithium metal negative electrode and significantly improving the cyclic performance of the lithium metal battery.

[0120] In summary, the PIMs material prepared by the superacid catalytic reaction of monomer 1 and monomer 2 of the present invention can form protection in lithium metal batteries, which can greatly reduce the occurrence of side reactions, make the morphology of lithium deposition smoother, greatly slow down the growth of lithium dendrites, and even solve the potential safety hazards of batteries from the source. The PIMs material prepared by the present invention has high mechanical strength and certain flexibility, can effectively cope with the volume change of the electrode during the charging and discharging process, and avoid the rupture and failure of the SEI layer. This is crucial to maintain the long-term stable operation of the battery.

[0121] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. An inherent microporous material, characterized in that: The inherent microporous material is prepared by a superacid catalytic reaction of monomer 1 and monomer 2; The monomer 1 is 4,4′-dihydroxybiphenyl and / or bisphenol AF; The monomer 2 is 2,2,2-trifluoroacetophenone.

2. The inherent microporous material according to claim 1, wherein The micropore diameter of the inherent microporous material is 0.4-2.0 nm; The molar ratio of monomer 1 to monomer 2 is 1:(0.5-2); The super acid catalytic reaction comprises: mixing monomer 1 and monomer 2 with dichloromethane and trifluoromethanesulfonic acid aqueous solution and sequentially stirring, washing and drying to obtain the inherent microporous material; Preferably, the solvent used for the washing is an alcohol solvent and / or an ether solvent.

3. A method for protecting a lithium metal negative electrode, characterized in that: The method comprises: S1: mixing and dispersing the inherent microporous material and the first protective solvent to obtain a protective mixed solution; The inherent microporous material is the inherent microporous material according to claim 1; S2: coating the protective mixed solution on the surface of the lithium metal negative electrode and performing a drying process to obtain a lithium metal negative electrode covered with an artificial SEI film.

4. The method for protecting a lithium metal negative electrode according to claim 3, wherein: The first protective solvent is an anhydrous pure solvent, preferably anhydrous acetonitrile and / or N-methylpyrrolidone; The concentration of the inherent microporous material in the protective mixed solution is 1-2wt%; The coating amount of the protective mixed solution on the surface of the lithium metal negative electrode is 15-40 μL·cm -2 ; The protective dispersion is coated on the surface of the lithium metal negative electrode by scraping, spraying, spin coating or dripping.

5. A lithium metal negative electrode covered with an artificial SEI film obtained by the protection method of a lithium metal negative electrode according to claim 3 or 4.

6. A lithium metal-based battery, characterized in that: The negative electrode of the battery is a lithium metal negative electrode covered with an artificial SEI film as claimed in claim 5; Preferably, the electrolyte of the battery is at least one of a carbonate electrolyte including a lithium salt, an ether electrolyte including a lithium salt, a sulfone electrolyte including a lithium salt, and a carboxylate electrolyte including a lithium salt; the lithium salt is at least one of lithium nitrate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, and lithium hexafluoroarsenate; Preferably, the lithium metal-based battery is a lithium-lithium symmetrical battery, a lithium-copper half-cell, a lithium ion battery, a lithium solid-state battery, a lithium sulfur battery, a lithium oxygen battery, a lithium nitrogen battery or a lithium carbon dioxide battery.

7. A method for protecting a lithium metal negative electrode, characterized in that: The method comprises: (1) mixing an intrinsic microporous material, lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide, and a second protective solvent to prepare a mixed slurry; The inherent microporous material is the inherent microporous material according to claim 1; (2) The mixed slurry is coated on the surface of a polytetrafluoroethylene plate and dried to obtain a solid electrolyte.

8. The method for protecting a lithium metal negative electrode according to claim 7, wherein: The second protective solvent is an anhydrous pure solvent, preferably at least one of anhydrous acetonitrile, N-methylpyrrolidone, chloroform, dimethyl sulfoxide and N,N-dimethylformamide; The mass fraction of the inherent microporous material in the mixed slurry is 5-20%; the molar ratio of lithium bis(trifluoromethanesulfonyl)imide to polyethylene oxide in the mixed slurry is 1:(10-30); the mass ratio of the inherent microporous material to polyethylene oxide is 1:(5-20); The film thickness of the mixed slurry on the surface of the polytetrafluoroethylene plate is 40-100 nm.

9. A solid electrolyte obtained by the method for protecting a lithium metal negative electrode according to claim 7 or 8.

10. A lithium metal-based battery, characterized in that: The electrolyte of the battery is the solid electrolyte according to claim 9; Preferably, the lithium metal-based battery is a lithium-lithium symmetrical battery, a lithium-copper half-cell, a lithium ion battery, a lithium solid-state battery, a lithium sulfur battery, a lithium oxygen battery, a lithium nitrogen battery or a lithium carbon dioxide battery.